STEM education in Malaysia towards developing a human capital through motivating science subject - Razali, Fazilah; Abdul Manaf, Umi Kalthom; Mohd Ayub, Ahmad Fauzi (Society for Research and Knowledge Management Ltd, 2020)
This paper focuses on the motivational factor in learning science encompassing the elements of self-efficacy, self-determination, intrinsic, grade, and career. These factors identified from previous research have a direct influence on the conception of careers related to Science, Technology, Engineering, and Mathematics (STEM) among students. This study is a quantitative study using two surveys: Motivational Science Questionnaire (MSQ II) and career interest in STEM from the STEM Student Questionnaire (S-STEM). The questionnaire was modified and tailored to the purpose of this investigation. The objective of this research is to determine motivation as the main factor in science to develop students’ interest in a STEM career among secondary students in Malaysia. A total of 419 Form Four students were the respondents of this study. The results show that motivation of indirect science learning can influence the development of Form 4 students’ interest in STEM careers. The data were analyzed using the Structural Equation Modeling (SEM) method which is in line with the self-determination theory to determine the strong influence of motivation on students’ career. The result shows a very high influence of motivation towards science with a significantly high variance of 51% on the development of interest in STEM-related careers among Malaysian students.